Influence of fatness, intelligence, education and sociodemographic factors on response rate in a health survey. Issue 4 (December 1989) - Sonne-Holm, S; Sørensen, T I; Jensen, G; Schnohr, P
Abstract : STUDY OBJECTIVE: The aim was to investigate the characteristics of non-responders to an invitation to attend a health examination. DESIGN: Taking advantage of an ongoing study of obesity, this was a survey of a cohort of severely obese men, with a randomly selected control group. PARTICIPANTS: The participants were draftees to the compulsory Danish military draft board examination between 1943 and 1977. Among 362, 200 draftees, 1940 were identified as severely obese (body mass index greater than or equal to 31 kg/m2). A comparison group of 1801 subjects was randomly drawn from the remaining population. During the period 1981-3 those still alive and living in the same region (1651 obese, 1504 control) were invited to a health examination. MEASUREMENTS AND MAIN RESULTS: The examination was attended by 964 obese (58%) and 1134 controls (75%). In both groups an increasing response rate was associated with decreasing body mass index, and increasing intelligence test score, educational level, current social class, age (up to 50 years) and proximity of residence. Logistic regression analysis showed that all these variables had independent effects on response rate. Frequency and duration of hospital admissions during the period 1977-82 did not differ among responders and non-responders in either group. CONCLUSION: Response rates in health surveys are strongly influenced by degree of fatness, intelligence, educational level, social class, age, and proximity of residence.